Association of Plasma Neurofilament Light with Postoperative Delirium. Issue 5 (15th September 2020) - Fong, Tamara G.; Vasunilashorn, Sarinnapha M.; Ngo, Long; Libermann, Towia A.; Dillon, Simon T.; Schmitt, Eva M.; Pascual‐Leone, Alvaro; Arnold, Steven E.; Jones, Richard N.; Marcantonio, Edward R.; Inouye, Sharon K.; ,
Abstract : Objective: To examine the association of the plasma neuroaxonal injury markers neurofilament light (NfL), total tau, glial fibrillary acid protein, and ubiquitin carboxyl‐terminal hydrolase L1 with delirium, delirium severity, and cognitive performance. Methods: Delirium case–no delirium control (n = 108) pairs were matched by age, sex, surgery type, cognition, and vascular comorbidities. Biomarkers were measured in plasma collected preoperatively (PREOP), and 2 days (POD2) and 30 days postoperatively (PO1MO) using Simoa technology (Quanterix, Lexington, MA). The Confusion Assessment Method (CAM) and CAM‐S (Severity) were used to measure delirium and delirium severity, respectively. Cognitive function was measured with General Cognitive Performance (GCP) scores. Results: Delirium cases had higher NfL on POD2 and PO1MO (median matched pair difference = 16.2pg/ml and 13.6pg/ml, respectively; p < 0.05). Patients with PREOP and POD2 NfL in the highest quartile (Q4) had increased risk for incident delirium (adjusted odds ratio [OR] = 3.7 [95% confidence interval (CI) = 1.1–12.6] and 4.6 [95% CI = 1.2–18.2], respectively) and experienced more severe delirium, with sum CAM‐S scores 7.8 points (95% CI = 1.6–14.0) and 9.3 points higher (95% CI = 3.2–15.5). At PO1MO, delirium cases had continued high NfL (adjusted OR = 9.7, 95% CI = 2.3–41.4), and those with Q4 NfL values showed a −2.3 point decline in GCP score (−2.3 points, 95% CI = −4.7 to −0.9). Interpretation: Patients with the highest PREOP or POD2 NfL levels were more likely to develop delirium. Elevated NfL at PO1MO was associated with delirium and greater cognitive decline. These findings suggest NfL may be useful as a predictive biomarker for delirium risk and long‐term cognitive decline, and once confirmed would provide pathophysiological evidence for neuroaxonal injury following delirium. ANN NEUROL 2020;88:984–994